1998
DOI: 10.1103/physrevb.57.1607
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of the deep boron acceptor in boron-doped6H-SiC

Abstract: A high-frequency ͑95 GHz͒ and conventional-frequency ͑9.3 GHz͒ pulsed electron paramagnetic resonance and electron-nuclear double resonance ͑ENDOR͒ study is reported on the deep boron acceptor in 6H-SiC. The results support a model in which the deep boron acceptor consists of a boron on a silicon position with an adjacent carbon vacancy. The carbon vacancy combines with a boron along the hexagonal c axis. It is concluded that 70-90 % of the spin density resides in the silicon dangling bonds surrounding the vac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
32
0
5

Year Published

2000
2000
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(39 citation statements)
references
References 25 publications
2
32
0
5
Order By: Relevance
“…19 Other groups proposed that this level is associated with a boron atom replacing a silicon atom with an adjacent carbon vacancy or an antisite with silicon in the carbon position. 20,21 It is believed that in the SiGe alloys, boron can act as a deeper defect under the influence of Fe i and Ge possibly explaining our observations. Following this scheme one can postulate a scenario for the behavior of the Fe i B pair in SiGe alloys.…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…19 Other groups proposed that this level is associated with a boron atom replacing a silicon atom with an adjacent carbon vacancy or an antisite with silicon in the carbon position. 20,21 It is believed that in the SiGe alloys, boron can act as a deeper defect under the influence of Fe i and Ge possibly explaining our observations. Following this scheme one can postulate a scenario for the behavior of the Fe i B pair in SiGe alloys.…”
Section: Resultsmentioning
confidence: 77%
“…At the same time, a second acceptor boron center, introducing a deeper level into the band gap with an activation energy about 0.65 eV, has been observed by some groups. [18][19][20] The origin of this deeper boron related acceptor level is uncertain and whether it corresponds to a deepening of the first shallow level caused by a nearby defect is still disputed. It has been suggested that it is connected with boron replacing a carbon atom ͑B C ͒.…”
Section: Resultsmentioning
confidence: 98%
“…Boron-related centers in SiC are known to have two key characteristics: a shallow acceptor with an ionization energy of about 0.30 eV and a deep level with an ionization energy of about 0.65 eV (Duijin-Arnold et al, 1998). While the nature of the shallow acceptor defect is accepted as an off-center substitutional boron atom at a silicon site (B Si ) (Duijin-Arnold et al, 1999), that of the deep boron-related level is not clear.…”
Section: Boron Diffusion In 4h-sic (A) Historic Backgroundmentioning
confidence: 99%
“…While the nature of the shallow acceptor defect is accepted as an off-center substitutional boron atom at a silicon site (B Si ) (Duijin-Arnold et al, 1999), that of the deep boron-related level is not clear. The B Si -V C pair (Duijin-Arnold et al, 1998) was refuted by ab initio calculations that suggest a B Si -Si C complex as a candidate (Aradi et al, 2001). In addition, candidates such as a substitutional boron atom at a carbon site (B C ) and a B C -C Si complex were also put forward (Bockstedte et al, 2001).…”
Section: Boron Diffusion In 4h-sic (A) Historic Backgroundmentioning
confidence: 99%
“…Therefore, although no conclusive proof has yet been shown, B Si is generally associated with the shallow acceptor, and it has been suggested [4] that B C might be the deep acceptor. On the other hand, substantial amounts of the deep boron acceptor could only be produced by implantation [5], so, in addition (based on theoretical calculations [6]) an "isomer" of B C , B Si + Si C , as well as (based on paramagnetic resonance studies [7]) a complex with a carbon vacancy, B Si + V C , were also suggested as possible origins of the "deep" boron center. The latter assignment was, however, not supported by the calculations, while B Si + Si C was predicted considerably higher in energy than B C .…”
mentioning
confidence: 98%